Pharmacokinetics and Excretion Study of Lycium barbarum Polysaccharides in Rats by FITC-Fluorescence Labeling - Hui Xia (MDPI AG, 2021)
A high-performance gel permeation chromatography fluorescence detection (HPGPC-FD) method combined with fluorescein isothiocyanate (FITC) labeling was established for the microanalysis of L. barbarum polysaccharides (LBP). The calibration curves linear over the range of 0.2–20 µg/mL in rat plasma, and 0.25–500 μg/mL in urine and feces samples with correlation coefficients greater than 0.99. The inter-day and intra-day precisions (RSD, %) of the method were under 15% with the relative recovery ranging from 84.6% to 104.0% and the RSD ranging from 0.47% to 7.28%. The concentration–time curve of LBP-FITC in plasma following intragastric administration at 100, 50 and 25 mg/kg well fitted to a nonlinear model. LBP-FITC slowly eliminated from plasma according to the long half-lives (t1/2 = 31.39, 38.09, and 45.76 h, respectively) and mean retention times (MRT0–t = 18.38, 19.15 and 20.07 h, respectively; AUC0–∞ = 230.49, 236.18 and 242.57 h, respectively) after administration of LBP-FITC at doses of 100, 50, and 25 mg/kg, respectively. After intragastric administration at 50 mg/kg for 72 h, the concentration of LBP-FITC in urine and feces was 0.09 ± 0.04% and 92.18 ± 3.61% respectively; the excretion rate of urine was the highest in 0–4 h period and decreased continuously in 4–24 h period. The excretion rate of feces was the highest in 4–10 h, 48.28 ± 9.349% in feces within 4–10 h, and decreased rapidly in 10–24 h. The present study showed that LBP was absorbed as its prototype and most proportion of LBP was excreted from feces, indicating a long time remaining in intestine.